Typification of the Linnaean name Centaurea sibirica (Asteraceae) - Altinordu, Fahim (Phytotaxa, 2016)
Centaurea Linnaeus (1753: 909) (Asteraceae) comprises a large number of taxa mainly occurring in the Mediterranean region and southwest Asia (Susanna & Garcia-Jacas 2007). The former wide concept of Centaurea resulted in a polyphyletic assemblage, and it has been recently split into several putatively monophyletic genera Centaurea, Psephellus Cass. and Rhaponticoides Vaill. (Wagenitz & Hellwig 2000; Greuter 2003; Hellwig 2004; Susanna & Garcia-Jacas 2007, 2009). Centaurea sibirica Linnaeus (1753: 913) is spreading from S Russia to W Siberia and Central Asia (Wagenitz & Hellwig 2000), it is one of the species of sixty-nine names in Centaurea described by Linnaeus and is currently accepted as Psephellus sibiricus (L.) Wagenitz (Wagenitz & Hellwig 2000: 37). However, from a nomenclatural standpoint, Centaurea sibirica has not been typified (Jarvis 2007, Ferrer-Gallego et al. 2014a, 2014b, 2014c, Altınordu & Ferrer-Gallego 2015, Ferrer-Gallego & Altınordu 2016, Iamonico & Peruzzi 2016). This paper designates a lectotype for C. sibirica based on the protologue and consultation of Linnaeus’s original material.